Clinical outcomes according to intentionality of acute pesticide poisoning in South Korea: retrospective observation study - Eujene Jung; Sung Hyun Lee; Hyun Ho Ryu (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate if intentional pesticide intake could have different clinical outcomes compared to unintentional poisoning, and whether acute alcohol consumption correlated with intentional poisoning. Method: The retrospective observational study was conducted in South Korea and comprised data from the Emergency Department-based Injury In-depth Surveillance Registry of all adults with pesticide poisoning from 2009 to 2017. The primary outcome was overall mortality. Adjusted odds ratios with 95% confidence intervals of the exposures on clinical outcomes were calculated. Data was analysed using SAS 9.4. Results: Among the 7,320 patients, intentional poisoning had higher odds of overall mortality (adjusted odds ratio: 1.88; 95% confidence interval: 1.56-2.25) and major adverse outcomes (adjusted odds ratio: 2.64; 95% confidence interval: 2.32-2.99), while acute alcohol consumption showed a higher incidence of intentional poisoning (adjusted odds ratio: 2.43; 95% confidence interval: 2.11-2.80). Conclusion: Intentional poisoning showed higher mortality rate and major adverse outcomes. It is important to consider host factors before poisoning, such as acute alcohol consumption, which may contribute to the clinical outcomes of pesticide poisoning cases. Key Words: Pesticide, Poisoning, Intentionality, Alcohol.